Development of Information System for Concrete Bridges Maintenance Quality Management System Based on Website to Improve Maintenance Performance - Janrivai Adiman Silalahi; Yusuf Latief; Naufal Budi Laksono (Jurnal Syntax Transformation, 2025)
Indonesia has thousands of national bridges that are vital for the country's mobility and economy. However, a large number of these bridges are in an unstable condition, posing a serious threat to the security and resilience of infrastructure. To keep the bridge safe and in good working order, ongoing maintenance and maintenance efforts are essential. The implementation of Quality Management Systems (SMM) and Knowledge Bases offers significant potential to improve bridge maintenance performance. However, the application of the Knowledge Base in the context of bridge maintenance is still very limited and has not been fully explored. Therefore, more research is needed to understand its impact and benefits in depth. The development of an effective Knowledge Base model and the integration of SMM in bridge maintenance work is a crucial strategic step to improve the performance and sustainability of bridge maintenance in Indonesia. These measures are expected to make a significant contribution to improving the resilience and safety of national bridge infrastructure.